Using a global botanic gardens database to help assess the capabilities of rare eucalypt species to cope with climate change. (3rd September 2015) - Booth, T.H.
Climate change impact analyses have focused mostly on natural distributions of plants and have generally ignored their intrinsic climatic adaptability. This may produce unreliable predictions of impacts. Eucalypts are potentially instructive for climate change studies, as many species have been assessed in commercial forestry trials outside the conditions of their natural distributions. However, rare eucalypt species, which usually have limited natural distributions, and are likely to be most susceptible to climate change, are often small or multi-stemmed species, which have generally not been included in commercial trials. This study used information for 12 rare eucalypt species from the PlantSearch database of Botanic Gardens Conservation International and assessed if this information can assist determining their climatic adaptability. The results should be treated with caution, but indicate that most of the 12 species are growing at some botanic gardens under annual mean temperature conditions that are warmer than where they occur naturally. Analyses d'impact du changement climatique ont porté essentiellement sur les distributions naturelles des plantes et ont généralement ignoré leur adaptabilité climatique intrinsèque. Cela peut produire des prédictions douteuses d'impacts. Les eucalyptus sont potentiellement instructive pour les études sur le changement climatique, que de nombreuses espèces ont été évaluées dans des expériences forestières commerciales en dehors des conditions de leurs distributions naturelles. Cependant, les espèces d'eucalyptus rares, qui ont généralement des distributions naturelles limitées, et sont susceptibles d'être plus vulnérables au changement climatique, sont souvent de petites ou à tiges multiples espèces, qui ne ont généralement pas été inclus dans des expériences commerciaux. Cette étude a utilisé l'information pour 12 rares espèces d'eucalyptus de la base de données des plantes des recherches de Botanic Gardens Conservation International et évaluée, si cette information peut aider à déterminer leur adaptabilité climatique. Les résultats doivent être traités avec prudence, mais indiquent que la plupart des 12 espèces croissent à des jardins botaniques sous température annuelle moyenne des conditions qui sont plus chaudes que le lieu où elles se produisent naturellement.Clima análisis del impacto del cambio se han centrado principalmente en la distribución natural de las plantas y en general han ignorado su adaptabilidad climática intrínseca. Este puede producir predicciones no fiables de impactos. Los eucaliptos son potencialmente instructivo para estudios sobre el cambio climático, ya que muchas especies se han evaluado en ensayos comerciales forestales fuera de las condiciones de sus distribuciones naturales. Sin embargo, raras especies de eucalipto, que normalmente tienen distribuciones naturales limitados, y es probable que sean más vulnerable al cambio climático, a menudo son pequeñas o ramas múltiples especies, que en general no han sido incluidos en los ensayos comerciales. Este estudio utilizó información de 12 especies de eucalipto raras de la base de datos de búsqueda de Plantas de Botanic Gardens Conservation International y evalúa si esta información puede ayudar a determinar su adaptabilidad climática. Los resultados deben ser tomados con cautela, pero indican que la mayoría de las 12 especies están creciendo en algunos jardines botánicos en condiciones de temperatura medias anuales que son más cálidas que en el que se producen naturalmente.